Evaluation of Centrifuged Bone Marrow on Bone Regeneration Around Implants in Rabbit Tibia - Betoni, Walter; Queiroz, Thallita P.; Luvizuto, Eloa R. [UNESP]; Valentini-Neto, Rodolpho; Garcia-Junior, Idelmo R.; Bernabe, Pedro F. E. [UNESP] (Lippincott Williams & Wilkins, 2012)
Objective: To evaluate the bone regeneration of cervical defects produced around titanium implants filled with blood clot and filled with centrifuged bone marrow (CBM) by means of histomorphometric analysis.Materials and Methods: Twelve rabbits received 2 titanium implants in each right tibia, with the upper cortical prepared with a 5-mm drill and the lower cortex with a 3-mm-diameter drill. Euthanasia was performed to allow analysis at 7, 21, and 60 days after operation. The samples were embedded in light curing resin, cut and stained with alizarin red and Stevenel blue for a histomorphometric analysis of the bone-to-implant contact (BIC) and the bone area around implant (BA). The values obtained were statistically analyzed using the nonparametric Kruskal-Wallis test (P = 0.05).Results: At 60 days postoperation, the groups had their cervical defects completely filled by neo-formed bone tissue. There was no statistically significant difference between the groups regarding BIC and BA during the analyzed periods.Conclusion: There was no difference in the bone repair of periimplant cervical defects with or without the use of CBM. (Implant Dent 2012;21:481-485)
Keywords: dental implants; bone marrow; clot